Mitochondrial and Glycolytic Capacity of Peripheral Blood Mononuclear Cells Isolated From Diverse Poultry Genetic Lines: Optimization and Assessment - Meyer, Meaghan M.; Lamont, Susan J.; Bobeck, Elizabeth A. (Frontiers in Veterinary Science, 2022)
Cellular metabolic preference is a culmination of environment, nutrition, genetics, and individual variation in poultry. The Seahorse XFe24 analyzer was used to generate foundational immune cellular metabolic data in layer, broiler, and legacy genetic strains using fresh chicken peripheral blood mononuclear cells (PBMC). Baseline mitochondrial respiration (Oxygen Consumption Rate; OCR) and glycolytic activity (Extracellular Acidification Rate; ECAR) were determined in modern commercial laying hen (Bovans White) and broiler (Ross 308) lines, as well as Iowa State University’s highly inbred lines (L8, Fayoumi M-15.2, Spanish, Ghs-6), partially inbred broiler line, and advanced intercrosses of broiler by Fayoumi M-15.2 and broiler by Leghorn lines. Commercial broiler versus Bovans layer and unvaccinated versus vaccinated Bovans layer immune cell metabolic potential were compared following an in-assay pathway inhibitor challenge. Titrations consistently showed that optimal PBMC density in laying hens and broilers was a 3 million cells per well monolayer. Assay media substrate titrations identified 25 mM glucose, 1mM glutamine, and 1mM sodium pyruvate as the optimal concentration for layer PBMC. Pathway inhibitor injection titrations in Bovans layers and broilers showed that 0.5 uM Carbonyl cyanide-4 phenylhydrazone (FCCP) and 1 uM oligomycin were optimal. Baseline OCR and ECAR were significantly affected by genetic line of bird (P<0.05), with the dual-purpose, L8 inbred line showing the highest OCR (mean 680 pmol/min), and the partially inbred broiler line showing the greatest ECAR (mean 74 mpH/min). ECAR metabolic potential tended to be greater in modern layers than broilers (P<0.10), indicating increased ability to utilize the glycolytic pathway to produce energy. OCR was significantly higher in vaccinated than unvaccinated hens (P<0.05), while baseline ECAR values were significantly lower in vaccinated Bovans laying hens, showing increased oxidative capacity in activated immune cells. These baseline data indicate that different genetic strains of birds utilized the mitochondrial respiration pathway differently and that modern commercial lines may have reduced immune cell metabolic capacity compared to legacy lines due to intense selection for production traits. Further, the Seahorse assay demonstrated ability to detect differences in cellular metabolism between genetic lines and immune status of chickens.